Bosnia’s attitude to the expansion of Islam in the first half of the 15th century - Wróbel, Piotr (Balcanica Posnaniensia. Acta et studia, 1997)
The article analyzes the situation of Bosnia in the face of the advancing Ottoman expansion during the first half of the fifteenth century. The research problem concerns the causes of the gradual subordination of the Bosnian state to the Ottoman Empire and the impact of internal conflicts and religious divisions on the weakening of the country. The aim of the study is to present the political and social mechanisms that led to Bosnia’s loss of independence. The author draws on historical sources and the findings of historiography concerning the history of medieval Bosnia and Ottoman expansion. The article demonstrates that after the death of King Tvrtko I, the country became engulfed in dynastic struggles and rivalry among powerful noble families. The Ottomans exploited these internal conflicts by supporting particular factions and gradually imposing political overlordship and the obligation to pay tribute. An additional destabilizing factor was the presence of the Bogomil heresy and tensions between Catholicism and Orthodoxy, which hindered cooperation with Hungary and the Christian world. The author points out that from as early as 1415 Bosnia had entered the Turkish sphere of influence, while subsequent Ottoman invasions and interventions only deepened its dependence. A certain improvement in the situation came only with the campaigns of Władysław III in 1443–1444, which temporarily reduced internal conflicts. The results of the analysis indicate that the political and social weakening of Bosnia determined its vulnerability to Ottoman expansion even before the final conquest of the country.